2004
DOI: 10.1038/labinvest.3700108
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant CpG island hypermethylation of multiple genes in colorectal neoplasia

Abstract: CpG island hypermethylation is a potential means of inactivating tumor suppressor genes, and many genes have been demonstrated to be hypermethylated and silenced in colorectal cancer. However, limited data is available upon the concurrent methylation of multiple genes in colorectal cancer and in its precursor lesion. To address changes in the methylation profiles of multiple genes during colorectal carcinogenesis, we investigated the methylation of 12 genes (APC, COX-2, DAP-kinase, E-cadherin, GSTP1, hMLH1, MG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
98
3
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 23 publications
(32 reference statements)
10
98
3
8
Order By: Relevance
“…The smaller numbers of epigenetic alterations detected in ACF compared to colorectal cancers from the same patients support the role of ACF as early precursors of some colorectal cancers; this follows the same trend reported for adenomas and colon cancers in a larger study. 22 Concordant methylation or lack of methylation of the same loci in both benign and malignant lesions from the same patients or methylation of cancers but not precursor lesions (Table II) was reported previously for small numbers of polyps and cancers. 9,15 Of particular interest were our findings of methylation in 11 ACF from 10 patients whose cancers lacked methylation of the same loci (Table II) and the lack of concordance of the same methylated loci among ACF from the same patients (Fig.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…The smaller numbers of epigenetic alterations detected in ACF compared to colorectal cancers from the same patients support the role of ACF as early precursors of some colorectal cancers; this follows the same trend reported for adenomas and colon cancers in a larger study. 22 Concordant methylation or lack of methylation of the same loci in both benign and malignant lesions from the same patients or methylation of cancers but not precursor lesions (Table II) was reported previously for small numbers of polyps and cancers. 9,15 Of particular interest were our findings of methylation in 11 ACF from 10 patients whose cancers lacked methylation of the same loci (Table II) and the lack of concordance of the same methylated loci among ACF from the same patients (Fig.…”
supporting
confidence: 73%
“…The smaller numbers of epigenetic alterations detected in ACF compared to colorectal cancers from the same patients support the role of ACF as early precursors of some colorectal cancers; this follows the same trend reported for adenomas and colon cancers in a larger study. 22 Concordant methylation or lack of methylation of the same loci in both benign and malignant lesions from the same patients or FIGURE 1 -ACF after staining intact human colonic mucosa with methylene blue (a, original magnification Â160; b, original magnification Â25). The methylation patterns of these ACF are illustrated in Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Other more limited studies on the methylation patterns of CAs are consistent with our observations and conclusions. [55][56][57][58] Five of the Group 1 genes (3OST2, HPP1, CDH13, CRBP1 and APC) were frequently methylated (>30%) in both CRCs and CAs. These genes may represent markers for risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we proceeded to examine the methylation status of the SPARC promoter, as aberrant methylation is commonly observed in colorectal cancers (Toyota et al, 1999;Lee et al, 2004), and recent studies in other cancers have revealed aberrant hypermethylation of the SPARC promoter to be responsible for low levels of SPARC expression (Sato et al, 2003;Suzuki et al, 2005;DiMartino et al, 2006). We were able to identify specific CpG sites that were consistently methylated in colorectal cancers by DNA bisulfite sequencing.…”
Section: Discussionmentioning
confidence: 99%